The Influence of University Logo Dimensions on Student Commitment in State Islamic Higher Education Institutions in South Kalimantan - Naldi, Muhammad Zikri; Juhaidi, Ahmad (South Sulawesi Education Development, 2026)
This study aims to measure the influence of the logo dimension of the Universitas Islam Negeri (UIN) Antasari Banjarmasin on student commitment. The university logo is seen not only as an aesthetic element, but also as a representation of the institution's values, benefits, and identity. The study used a quantitative approach with a predictive causal design through an online questionnaire distributed using convenience sampling and snowball sampling techniques, resulting in 408 respondents from a total population of 12,422 students. The research instrument was in the form of a Likert scale questionnaire adapted from Park et al. (2013) and analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results showed that the identification, functional benefits, and expressive appearance of logos had a significant effect on student commitment, while aesthetics had no effect. An R² value of 0.523 indicates that 52.3% of the variation in student commitment can be explained by the university logo. This study confirm that student commitment can be strengthened through the management of logos that represent the identity and benefits of the institution, not just highlighting visual beauty.